Catalyst slurry and preparation method thereof, membrane electrode and electrolytic cell
By adding dispersant to the catalyst slurry, the unevenness problem caused by catalyst settlement is solved, and the stability of the catalyst slurry and the performance of the membrane electrode are improved.
Patent Information
- Application Number
- CN202510592586.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-08
- Publication Date
- 2025-08-15
AI Technical Summary
The catalyst in the catalyst slurry is prone to settle, resulting in uneven loading of the membrane electrode catalyst, affecting performance.
Add dispersants such as polyvinylpyrrolidone, polyvinyl alcohol, polyethyleneimine, cetyltrimethylammonium bromide and hydroxyethyl cellulose to the catalyst slurry to stabilize the Zeta potential or form steric hindrance to reduce settlement by adsorption and surround the surface of the catalyst particles.
The stability and uniformity of the catalyst slurry are improved, the uniformity of the catalyst load in the membrane electrode is ensured, and the performance and service life of the membrane electrode are enhanced.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of hydrogen production by electrolysis of water, and in particular to a catalyst slurry and a preparation method thereof, a membrane electrode, and an electrolytic cell. Background Art
[0002] The membrane electrode (MEA) is the core component of an electrolyzer. Its performance depends primarily on the catalyst within it, which in turn is affected by the catalyst slurry preparation and spraying. The catalyst in the slurry is typically a high-density metal or metal oxide. Once dispersed, these metals or metal oxides are prone to sedimentation during storage, which can lead to uneven catalyst loading on the MEA prepared from a single batch of catalyst slurry, thus affecting MEA performance. Summary of the Invention
[0003] The embodiments of the present application provide a catalyst slurry and a preparation method thereof, a membrane electrode, and an electrolyzer. The catalyst slurry can slow down sedimentation and ensure the uniformity of catalyst loading in different membrane electrodes prepared from a single batch of catalyst slurry.
[0004] In a first aspect, an embodiment of the present application provides a catalyst slurry comprising a catalyst, a proton exchange resin, a dispersant, and a solvent;
[0005] The dispersant includes at least one of polyvinyl pyrrolidone, polyvinyl alcohol, polyethylene imine, hexadecyltrimethylammonium bromide and hydroxyethyl cellulose.
[0006] In some embodiments, the dispersant includes polyvinylpyrrolidone and polyethyleneimine;
[0007] and / or, the dispersant comprises polyvinyl pyrrolidone and cetyltrimethylammonium bromide;
[0008] And / or, the dispersant includes cetyltrimethylammonium bromide and hydroxyethyl cellulose.
[0009] In some embodiments, the mass percentage of the dispersant in the catalyst slurry is 0.1% to 5%.
[0010] In some embodiments, the particle size D90 of the catalyst slurry is 280 nm to 350 nm.
[0011] In some embodiments, the zeta potential of the catalyst slurry is -35 mV to -50 mV.
[0012] In some embodiments, the initial solid content of the catalyst slurry is 1% to 20% by mass.
[0013] In some embodiments, after standing at room temperature for 1 hour, the sedimentation retention rate of the catalyst slurry is ≥95%.
[0014] In a second aspect, an embodiment of the present application further provides a method for preparing a catalyst slurry, which is used to prepare the catalyst slurry as described above, comprising:
[0015] Proton exchange resin is provided;
[0016] adding a proton exchange resin to a solvent to obtain a first mixed solution;
[0017] adding a catalyst to the first mixed solution to obtain a second mixed solution;
[0018] adding a dispersant to the second mixed solution to obtain a third mixed solution;
[0019] The third mixed solution is dispersed to obtain catalyst slurry.
[0020] In some embodiments, dispersing the third mixed solution comprises:
[0021] The third mixed solution is subjected to shearing treatment and cell pulverization treatment.
[0022] In some embodiments, the shearing treatment is performed under the following conditions: a rotation speed of 200 rpm / min to 600 rpm / min and a shearing time of 10 min to 60 min.
[0023] In some embodiments, the cell disruption treatment is performed under the following conditions: a temperature of -5°C to 5°C, an ultrasonic power of 50 kW to 150 kW, and ultrasonic treatment for 10 min to 60 min.
[0024] In a third aspect, an embodiment of the present application further provides a membrane electrode, comprising a catalyst layer;
[0025] The catalyst layer is prepared by using the catalyst slurry as described above, or by using the catalyst slurry prepared by the catalyst slurry preparation method as described above.
[0026] In a fourth aspect, an embodiment of the present application further provides an electrolytic cell comprising the membrane electrode as described above.
[0027] Beneficial effects of the embodiments of the present application:
[0028] In an embodiment of the present application, a catalyst slurry comprises a catalyst, a proton exchange resin, a dispersant and a solvent. Wherein, the dispersant comprises at least one of polyvinyl pyrrolidone, polyvinyl alcohol, polyethyleneimine, hexadecyltrimethylammonium bromide and hydroxyethyl cellulose. By adding a dispersant to the catalyst slurry, and the dispersant comprises at least one of polyvinyl pyrrolidone, polyvinyl alcohol, polyethyleneimine, hexadecyltrimethylammonium bromide and hydroxyethyl cellulose, the dispersant can be adsorbed on the surface of colloidal particles such as the catalyst in the catalyst slurry, thereby stabilizing the Zeta potential of the catalyst slurry, or the dispersant surrounds the colloidal particles such as the catalyst in the catalyst slurry, forming a steric hindrance, reducing the agglomeration of the colloidal particles, and then slowing down the sedimentation of the catalyst slurry, and improving the stability of the catalyst slurry. In other words, the catalyst slurry provided in the embodiment of the present application can slow down sedimentation, improve the stability of the catalyst slurry, ensure the uniformity of the catalyst loading in different membrane electrodes prepared by a single batch of catalyst slurry, and improve stability. DETAILED DESCRIPTION
[0029] The technical solutions in the embodiments of the present application will be described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of the present application. In addition, it should be understood that the specific embodiments described herein are only used to illustrate and explain the present application and are not intended to limit the present application.
[0030] In a first aspect, embodiments of the present application provide a catalyst slurry comprising a catalyst, a proton exchange resin, a dispersant, and a solvent, wherein the dispersant comprises at least one of polyvinyl pyrrolidone, polyvinyl alcohol, polyethyleneimine, cetyltrimethylammonium bromide, and hydroxyethyl cellulose.
[0031] The embodiment of the present application adds a dispersant to the catalyst slurry, and the dispersant includes at least one of polyvinyl pyrrolidone, polyvinyl alcohol, polyethyleneimine, hexadecyltrimethylammonium bromide and hydroxyethyl cellulose, so that the dispersant can be adsorbed on the surface of colloidal particles such as the catalyst in the catalyst slurry, thereby stabilizing the Zeta potential of the catalyst slurry, or the dispersant surrounds the colloidal particles such as the catalyst in the catalyst slurry to form a steric hindrance, reduce the agglomeration of the colloidal particles, and then slow down the sedimentation of the catalyst slurry and improve the stability of the catalyst slurry. In other words, the catalyst slurry provided by the embodiment of the present application can slow down the sedimentation, improve the stability of the catalyst slurry, ensure the uniformity of the catalyst loading in different membrane electrodes prepared by a single batch of catalyst slurry, and improve stability.
[0032] Among them, the dispersant in the catalyst slurry provided in the embodiment of the present application includes an ionic dispersant (such as polyethyleneimine and hexadecyltrimethylammonium bromide) and a non-ionic dispersant (such as polyvinylpyrrolidone, polyvinyl alcohol and hydroxyethyl cellulose). After being added to the catalyst slurry, the ionic dispersant can ionize positive ions and negative ions, and the positive ions and negative ions can be adsorbed on the surface of colloidal particles such as the catalyst to form a double electric layer, thereby improving the Zeta potential of the catalyst slurry, ensuring the stability of the catalyst slurry, and slowing down the sedimentation of the catalyst slurry. After the non-ionic dispersant is added to the catalyst slurry, it can be adsorbed on the surface of colloidal particles such as the catalyst, surrounding the colloidal particles to form a steric hindrance, reducing the phenomenon of colloidal particle agglomeration, and then achieving the dispersion of the colloidal particles, slowing down the sedimentation phenomenon formed by the agglomeration of the colloidal particles.
[0033] Polyvinylpyrrolidone (PVP) can promote the uniform dispersion of the catalyst in the catalyst slurry. Its surface polar groups can form stable hydrogen bonds, allowing it to adsorb onto the surfaces of colloidal particles such as the catalyst in the catalyst slurry, increasing the steric hindrance of the colloidal particles and ensuring the stability of the catalyst slurry. PVP also has excellent film-forming properties. During the preparation of the catalyst slurry into a membrane electrode, it helps form a uniform and dense membrane structure, thereby improving the performance of the membrane electrode. Furthermore, PVP has good chemical stability and is not prone to reacting with other components in the catalyst slurry, ensuring the long-term stability of the slurry.
[0034] Polyvinyl alcohol (PVA) is a high molecular polymer. When added to the catalyst slurry, it can increase the viscosity of the slurry, which helps to improve the suspension stability of colloidal particles such as catalysts in the catalyst slurry. At the same time, the hydroxyl functional groups on polyvinyl alcohol can form hydrogen bonds and van der Waals forces with colloidal particles such as catalysts in the catalyst slurry, thereby reducing the mutual aggregation between colloidal particles, ensuring uniform dispersion, and reducing sedimentation. In addition, when the catalyst slurry is prepared into a membrane electrode, polyvinyl alcohol can also improve the bonding force between the membrane electrode and the substrate, thereby improving the adhesion performance. Polyvinyl alcohol also helps to form a smooth and tough membrane structure, thereby improving the mechanical strength and durability of the membrane electrode.
[0035] Polyethyleneimine (PEI) has high cationicity and amine functional groups, which can effectively reduce the sedimentation of colloidal particles such as catalysts in catalyst slurries through electrostatic attraction. Polyethyleneimine can also increase the zeta potential of colloidal particles such as catalysts in the catalyst slurry, thereby increasing the electrostatic repulsion between the colloidal particles, effectively reducing sedimentation and improving the stability of the dispersed system. Furthermore, polyethyleneimine has good electrical conductivity, which helps improve the electron transfer efficiency of the membrane electrode. It also has good chemical stability and environmental friendliness.
[0036] Cetyltrimethylammonium bromide (CTAB) is a cationic dispersant containing positively charged quaternary ammonium groups in its molecular structure. The cations in CTAB can adsorb and neutralize the negatively charged colloidal particles in the catalyst slurry, increasing the zeta potential of the catalyst slurry, ensuring its stability, and slowing its sedimentation. CTAB also contains alkyl chains that form a bridging structure, reducing the sedimentation of colloidal particles in the catalyst slurry. Furthermore, CTAB forms a protective film on the catalyst surface, extending the service life of the membrane electrode.
[0037] Hydroxyethyl cellulose (HEC) is a nonionic cellulose ether with excellent thickening properties. It can increase the viscosity of the catalyst slurry, allowing for better dispersion of colloidal particles such as the catalyst. It also forms a stable colloidal structure, surrounding the colloidal particles and reducing sedimentation. Furthermore, HEC has excellent water retention properties, preventing rapid water loss after coating of the catalyst slurry, which can lead to uneven membrane electrode structures.
[0038] It is understood that in the catalyst slurry provided in the embodiments of the present application, the dispersant may include only one of polyvinyl pyrrolidone, polyvinyl alcohol, polyethyleneimine, cetyltrimethylammonium bromide, and hydroxyethyl cellulose, or a combination of multiple dispersants. When a combination of multiple dispersants is used, it may include only ionic dispersants, only non-ionic dispersants, or a combination of ionic and non-ionic dispersants.
[0039] In some embodiments, the dispersant includes polyvinylpyrrolidone and polyethyleneimine. Polyvinylpyrrolidone (PVP) forms a steric barrier on the particle surface through long-chain molecules to prevent direct contact between the particles; polyethyleneimine (PEI) provides charge neutralization through a large number of amino groups, which can stabilize the surface charge of the particles, especially under acidic conditions. The combination of the two can simultaneously inhibit van der Waals forces and electrostatic attraction, achieving more stable dispersion. The hydrophobic segment of PVP and the amino group of PEI may produce synergistic adsorption, enhancing coverage of the particle surface and ensuring dispersion effect and stability.
[0040] In some embodiments, the dispersant includes polyvinylpyrrolidone and cetyltrimethylammonium bromide. Polyvinylpyrrolidone (PVP) wraps the surface of the particles through its long-chain molecules to form a steric hindrance layer, which can effectively prevent the particles from agglomerating. Cetyltrimethylammonium bromide (CTAB) can be adsorbed on the surface of the particles through the cationic head group, providing electrostatic repulsion. The synergistic effect of the two can simultaneously suppress the van der Waals force and electrostatic attraction of the particles, thereby achieving a more stable dispersion effect. In addition, the branched structure in PVP can produce complementary adsorption with the benzene ring and long carbon chain in CTAB, thereby enhancing the uniformity of coverage on the particle surface and improving the dispersion effect and stability.
[0041] In some embodiments, the dispersant includes cetyltrimethylammonium bromide and hydroxyethyl cellulose. Cetyltrimethylammonium bromide (CTAB) is adsorbed on the particle surface through the cationic head group, forming an electrostatic repulsion layer, which can effectively stabilize the particles, especially under acidic conditions. Hydroxyethyl cellulose (HEC) can wrap the particles through long-chain molecules, providing a steric hindrance effect. The combination of the two can simultaneously suppress van der Waals forces and electrostatic attraction, achieving a more stable dispersion. The hydrophobic carbon chain of CTAB and the hydroxyl group of HEC may produce synergistic adsorption, enhancing the coverage of the particle surface, thereby enhancing the uniformity of the coverage of the particle surface and improving the dispersion effect and stability.
[0042] In some embodiments, the mass percentage of the dispersant in the catalyst slurry is 0.1% to 5%. By setting the mass percentage of the dispersant in the catalyst slurry to 0.1% to 5%, the dispersion effect can be ensured, and the viscosity of the catalyst slurry can be maintained within an appropriate range, thereby ensuring the conductivity and electrochemical performance of the prepared membrane electrode.
[0043] Illustratively, the mass percentage of the dispersant in the catalyst slurry may be 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%.
[0044] In some embodiments, the particle size D90 of the catalyst slurry is 280 nm to 350 nm.
[0045] The particle size D90 of the catalyst slurry refers to the particle size D90 of the colloidal particles in the catalyst slurry, and the colloidal particles can be formed by materials such as the catalyst, proton exchange resin, and dispersant in the catalyst slurry. The larger the average particle size of the colloidal particles, the easier it is to settle during standing. The particle size D90 of the catalyst slurry provided in the embodiment of the present application is controlled within the range of 280nm to 350nm, which can have better dispersibility and stability and reduce the sedimentation phenomenon of the catalyst slurry. In addition, the particle size D90 of the catalyst slurry is controlled to 280nm to 350nm, which also helps to expose the active sites of the catalyst in the catalyst slurry, exert better catalytic performance, and after forming the membrane electrode by coating or spraying, it can reduce the surface defects of the membrane electrode and ensure the performance and service life of the membrane electrode.
[0046] In some embodiments, the zeta potential of the catalyst slurry is -35 mV to -50 mV.
[0047] Zeta potential is an important indicator for characterizing the stability of colloidal dispersions. It can reflect the potential difference between the surface of colloidal particles and the surrounding fluid. In a colloidal system, a layer of ions is often adsorbed on the surface of colloidal particles to form a double-layer structure. These ions interact with the charges on the surface of the colloidal particles, forming an electric field around the colloidal particles, and the Zeta potential is the potential value of this electric field on the shear surface. The smaller the colloidal particles, the higher the absolute value of the Zeta potential (positive or negative), and the more stable the system. This is because a high Zeta potential means that the electrostatic repulsion between colloidal particles is large, which can effectively resist the aggregation and sedimentation of colloidal particles.
[0048] The Zeta potential of the catalyst slurry provided in the embodiment of the present application is -35mV to -50mV, which can effectively reduce the aggregation phenomenon between the colloidal particles, thereby reducing the occurrence of sedimentation and ensuring the stability of the catalyst slurry.
[0049] In some embodiments, the initial solid content of the catalyst slurry is 1% to 20% by mass.
[0050] The initial solids content of the catalyst slurry refers to the percentage by mass of solid components in the initial state after the catalyst slurry is prepared. By setting the initial solids content of the catalyst slurry within the range of 1% to 20%, the dispersion of the membrane electrode can be guaranteed, and the catalyst slurry has good fluidity, which facilitates uniform coating and produces a membrane electrode with uniform thickness. Setting the initial solids content of the catalyst slurry within the range of 1% to 20% also helps the resulting membrane electrode have good conductivity and service life, while ensuring the utilization rate of raw materials.
[0051] Illustratively, the initial solids content of the catalyst slurry can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20% by mass.
[0052] In some embodiments, after standing at room temperature for 1 hour, the sedimentation retention rate of the catalyst slurry is ≥95%.
[0053] The sedimentation retention rate refers to the ratio of the current solid content to the initial solid content of the slurry after it has been allowed to stand for a period of time. The catalyst slurry provided in the examples of this application has a sedimentation retention rate of over 95%, which ensures the long-term storage stability of the catalyst slurry and maintains a good dispersion state. This ensures smooth coating or spraying, as well as drying and curing steps, improves the stability and controllability of the processing, and ensures that the membrane electrode prepared from a single batch of catalyst slurry has good uniformity.
[0054] In some embodiments, the catalyst may be at least one of nickel ferrite, platinum-on-carbon, and platinum-on-ruthenium-on-carbon. Nickel ferrite can be used as a catalyst for hydrogen production by electrolysis of water. By reducing the activation energy of water electrolysis, it improves electrolysis efficiency, thereby increasing hydrogen production. Nickel ferrite has high catalytic activity, good stability, and low cost.
[0055] It is understandable that those skilled in the art can select a catalyst according to actual needs, and the catalyst provided in the examples of the present application is not intended to limit the scope of protection of the present application.
[0056] In some embodiments, the solvent may be ethanol. Ethanol has good solubility and dispersibility for the catalyst, proton exchange resin, and dispersant, and can improve the dispersion and stability of the catalyst slurry. Ethanol also has appropriate surface tension, which helps to reduce the generation of bubbles in the process of preparing the catalyst layer from the catalyst slurry, thereby improving the quality of the catalyst layer. Ethanol has appropriate volatility, which can ensure the stability of the catalyst slurry during storage. At the same time, after coating or spraying, the ethanol can be rapidly volatilized by changing conditions such as temperature, thereby promoting the rapid formation and solidification of the catalyst layer.
[0057] In some embodiments, the proton exchange resin includes at least one of a perfluorosulfonic acid resin, a polystyrene-divinylbenzene copolymer type resin, and a polyethylene naphthalate resin.
[0058] The proton exchange resin in the catalyst slurry can play the role of ion conduction, which can help protons to be efficiently transported and improve electrolysis efficiency. It can also act as a binder to enable the catalyst to achieve good adhesion and ensure the structural stability and catalytic activity of the catalyst layer.
[0059] In a second aspect, an embodiment of the present application further provides a method for preparing a catalyst slurry, which is used to prepare the catalyst slurry as described above, comprising:
[0060] Proton exchange resin is provided;
[0061] adding a proton exchange resin to a solvent to obtain a first mixed solution;
[0062] adding a catalyst to the first mixed solution to obtain a second mixed solution;
[0063] adding a dispersant to the second mixed solution to obtain a third mixed solution;
[0064] The third mixed solution is dispersed to obtain catalyst slurry.
[0065] The preparation method of the catalyst slurry provided in the embodiment of the present application has all the beneficial effects of the catalyst slurry described above, which will not be repeated here.
[0066] In some embodiments, dispersing the third mixed solution comprises:
[0067] The third mixed solution is subjected to shearing treatment and cell pulverization treatment.
[0068] By subjecting the third mixed solution to shearing and cell crushing treatments, the particle size of the colloidal particles therein can be refined, which helps to improve the dispersion performance, reduce sedimentation, and ensure the catalytic activity of the catalyst in the prepared membrane electrode, thereby improving the coating or spraying performance of the catalyst slurry during the preparation of the membrane electrode, and forming a uniform and dense membrane electrode.
[0069] In some embodiments, the shearing treatment is performed under the following conditions: a rotation speed of 200 rpm / min to 600 rpm / min and a shearing time of 10 min to 60 min.
[0070] Shearing at a speed of 200-600 rpm ensures strong shear force, dispersing particles, fibers, or clusters in the third mixed solution, improving dispersion uniformity and stability. High-speed shearing refines the colloidal particles in the resulting catalyst slurry and reduces sedimentation. Setting the shearing time to 10-60 minutes ensures effective shearing.
[0071] Illustratively, during the shearing process, the rotation speed can be set to 200rpm / min, 250rpm / min, 300rpm / min, 350rpm / min, 400rpm / min, 450rpm / min, 500rpm / min, 550rpm / min or 600rpm / min, and the shearing time can be set to 10min, 15min, 20min, 25min, 30min, 35min, 40min, 45min, 50min, 55min or 60min.
[0072] In some embodiments, the cell disruption treatment is performed under the following conditions: a temperature of -5°C to 5°C, an ultrasonic power of 50 kW to 150 kW, and ultrasonic treatment for 10 min to 60 min.
[0073] Cell pulverization treatment is a technology that uses external force to destroy the cell membrane or cell wall to release the cell contents. In the embodiment of the present application, the cell pulverization treatment is to treat the third mixed solution by ultrasonic treatment. By performing ultrasonic treatment under low temperature conditions (-5°C to 5°C), the stability of the components in the third mixed solution can be guaranteed, and chemical changes or degradation phenomena can be reduced. By setting the ultrasonic power to 50kW to 150kW, the third mixed solution can generate strong shock waves and microjets, thereby refining the colloidal particles in the third mixed solution to a smaller particle size range and improving the dispersion effect. The ultrasonic treatment time is 10min to 60min, which can ensure the dispersion and refinement effects.
[0074] Illustratively, during the cell disruption treatment, the ultrasonic power can be set to 50kW, 55kW, 60kW, 65kW, 70kW, 75kW, 80kW, 85kW, 90kW, 95kW, 100kW, 105kW, 110kW, 115kW, 120kW, 125kW, 130kW, 135kW, 140kW, 145kW or 150kW, and the ultrasonic treatment time can be set to 10min, 15min, 20min, 25min, 30min, 35min, 40min, 45min, 50min, 55min or 60min.
[0075] In a third aspect, embodiments of the present application further provide a membrane electrode, comprising a catalyst layer. The catalyst layer is prepared using the catalyst slurry described above, or a catalyst slurry prepared using the catalyst slurry preparation method described above.
[0076] The membrane electrode provided in the embodiment of the present application has all the beneficial effects of the catalyst slurry as described above, which will not be repeated here.
[0077] In a fourth aspect, an embodiment of the present application further provides an electrolytic cell comprising the membrane electrode as described above.
[0078] The electrolytic cell provided in the embodiment of the present application has the beneficial effects of the catalyst slurry as described above, which will not be repeated here.
[0079] In some embodiments, the electrolyzer is a water electrolyzer, which can produce hydrogen by electrolyzing water.
[0080] The following examples are further described in conjunction with specific embodiments. It should be understood that these embodiments are intended to illustrate the present invention only and are not intended to limit the scope of the present invention. The experimental methods in the following examples where specific conditions are not specified are generally based on the conditions recommended by the manufacturer.
[0081] Example 1
[0082] (1) adding perfluorosulfonic acid resin to ethanol to obtain a first mixed solution;
[0083] (2) adding nickel ferrite to the first mixed solution to obtain a second mixed solution;
[0084] (3) adding polyvinyl pyrrolidone to the second mixed solution to obtain a third mixed solution;
[0085] (4) The third mixed solution was sheared for 30 min at a rotation speed of 400 rpm / min, and then ultrasonically treated for 30 min at a temperature of 0° C. and an ultrasonic power of 100 kW to obtain a catalyst slurry.
[0086] The mass percentage of the dispersant in the catalyst slurry is 2.5%, and the initial solid content of the catalyst slurry is 10%.
[0087] Example 2
[0088] (1) adding perfluorosulfonic acid resin to ethanol to obtain a first mixed solution;
[0089] (2) adding nickel ferrite to the first mixed solution to obtain a second mixed solution;
[0090] (3) adding polyvinyl alcohol to the second mixed solution to obtain a third mixed solution;
[0091] (4) The third mixed solution was sheared for 30 min at a rotation speed of 400 rpm / min, and then ultrasonically treated for 30 min at a temperature of 0° C. and an ultrasonic power of 100 kW to obtain a catalyst slurry.
[0092] The mass percentage of the dispersant in the catalyst slurry is 2.5%, and the initial solid content of the catalyst slurry is 10%.
[0093] Example 3
[0094] (1) adding perfluorosulfonic acid resin to ethanol to obtain a first mixed solution;
[0095] (2) adding nickel ferrite to the first mixed solution to obtain a second mixed solution;
[0096] (3) adding polyethyleneimine to the second mixed solution to obtain a third mixed solution;
[0097] (4) The third mixed solution was sheared for 30 min at a rotation speed of 400 rpm / min, and then ultrasonically treated for 30 min at a temperature of 0° C. and an ultrasonic power of 100 kW to obtain a catalyst slurry.
[0098] The mass percentage of the dispersant in the catalyst slurry is 2.5%, and the initial solid content of the catalyst slurry is 10%.
[0099] Example 4
[0100] (1) adding perfluorosulfonic acid resin to ethanol to obtain a first mixed solution;
[0101] (2) adding nickel ferrite to the first mixed solution to obtain a second mixed solution;
[0102] (3) adding hexadecyltrimethylammonium bromide to the second mixed solution to obtain a third mixed solution;
[0103] (4) The third mixed solution was sheared for 30 min at a rotation speed of 400 rpm / min, and then ultrasonically treated for 30 min at a temperature of 0° C. and an ultrasonic power of 100 kW to obtain a catalyst slurry.
[0104] The mass percentage of the dispersant in the catalyst slurry is 2.5%, and the initial solid content of the catalyst slurry is 10%.
[0105] Example 5
[0106] (1) adding perfluorosulfonic acid resin to ethanol to obtain a first mixed solution;
[0107] (2) adding nickel ferrite to the first mixed solution to obtain a second mixed solution;
[0108] (3) adding hydroxyethyl cellulose to the second mixed solution to obtain a third mixed solution;
[0109] (4) The third mixed solution was sheared for 30 min at a rotation speed of 400 rpm / min, and then ultrasonically treated for 30 min at a temperature of 0° C. and an ultrasonic power of 100 kW to obtain a catalyst slurry.
[0110] The mass percentage of the dispersant in the catalyst slurry is 2.5%, and the initial solid content of the catalyst slurry is 10%.
[0111] Example 6
[0112] (1) adding perfluorosulfonic acid resin to ethanol to obtain a first mixed solution;
[0113] (2) adding nickel ferrite to the first mixed solution to obtain a second mixed solution;
[0114] (3) adding polyvinyl pyrrolidone to the second mixed solution to obtain a third mixed solution;
[0115] (4) The third mixed solution was sheared at a rotation speed of 200 rpm / min for 60 min, and then ultrasonically treated at a temperature of 0° C. and an ultrasonic power of 150 kW for 10 min to obtain a catalyst slurry.
[0116] The mass percentage of the dispersant in the catalyst slurry is 2.5%, and the initial solid content of the catalyst slurry is 10%.
[0117] Example 7
[0118] (1) adding perfluorosulfonic acid resin to ethanol to obtain a first mixed solution;
[0119] (2) adding nickel ferrite to the first mixed solution to obtain a second mixed solution;
[0120] (3) adding polyvinyl pyrrolidone to the second mixed solution to obtain a third mixed solution;
[0121] (4) The third mixed solution was sheared for 10 min at a rotation speed of 600 rpm / min, and then ultrasonically treated for 60 min at a temperature of 0° C. and an ultrasonic power of 50 kW to obtain a catalyst slurry.
[0122] The mass percentage of the dispersant in the catalyst slurry is 2.5%, and the initial solid content of the catalyst slurry is 10%.
[0123] Example 8
[0124] (1) adding perfluorosulfonic acid resin to ethanol to obtain a first mixed solution;
[0125] (2) adding nickel ferrite to the first mixed solution to obtain a second mixed solution;
[0126] (3) adding polyvinyl pyrrolidone to the second mixed solution to obtain a third mixed solution;
[0127] (4) The third mixed solution was sheared for 30 minutes at a rotation speed of 400 rpm / min to obtain a catalyst slurry.
[0128] The mass percentage of the dispersant in the catalyst slurry is 2.5%, and the initial solid content of the catalyst slurry is 10%.
[0129] Example 9
[0130] (1) adding perfluorosulfonic acid resin to ethanol to obtain a first mixed solution;
[0131] (2) adding nickel ferrite to the first mixed solution to obtain a second mixed solution;
[0132] (3) adding polyvinyl pyrrolidone to the second mixed solution to obtain a third mixed solution;
[0133] (4) The third mixed solution was ultrasonically treated for 30 minutes at a temperature of 0° C. and an ultrasonic power of 100 kW to obtain a catalyst slurry.
[0134] The mass percentage of the dispersant in the catalyst slurry is 2.5%, and the initial solid content of the catalyst slurry is 10%.
[0135] Example 10
[0136] (1) adding perfluorosulfonic acid resin to ethanol to obtain a first mixed solution;
[0137] (2) adding nickel ferrite to the first mixed solution to obtain a second mixed solution;
[0138] (3) adding polyvinyl pyrrolidone to the second mixed solution to obtain a third mixed solution;
[0139] (4) The third mixed solution was sheared for 30 min at a rotation speed of 400 rpm / min, and then ultrasonically treated for 30 min at a temperature of 0° C. and an ultrasonic power of 100 kW to obtain a catalyst slurry.
[0140] The mass percentage of the dispersant in the catalyst slurry is 0.1%, and the initial solid content of the catalyst slurry is 1%.
[0141] Example 11
[0142] (1) adding perfluorosulfonic acid resin to ethanol to obtain a first mixed solution;
[0143] (2) adding nickel ferrite to the first mixed solution to obtain a second mixed solution;
[0144] (3) adding polyvinyl pyrrolidone to the second mixed solution to obtain a third mixed solution;
[0145] (4) The third mixed solution was sheared for 30 min at a rotation speed of 400 rpm / min, and then ultrasonically treated for 30 min at a temperature of 0° C. and an ultrasonic power of 100 kW to obtain a catalyst slurry.
[0146] The mass percentage of the dispersant in the catalyst slurry is 5%, and the initial solid content of the catalyst slurry is 20%.
[0147] Example 12
[0148] (1) adding perfluorosulfonic acid resin to ethanol to obtain a first mixed solution;
[0149] (2) adding nickel ferrite to the first mixed solution to obtain a second mixed solution;
[0150] (3) adding polyvinyl pyrrolidone to the second mixed solution to obtain a third mixed solution;
[0151] (4) The third mixed solution was sheared for 30 min at a rotation speed of 400 rpm / min, and then ultrasonically treated for 30 min at a temperature of 0° C. and an ultrasonic power of 100 kW to obtain a catalyst slurry.
[0152] The mass percentage of the dispersant in the catalyst slurry is 2.5%, and the initial solid content of the catalyst slurry is 2%.
[0153] Example 13
[0154] (1) adding perfluorosulfonic acid resin to ethanol to obtain a first mixed solution;
[0155] (2) adding nickel ferrite to the first mixed solution to obtain a second mixed solution;
[0156] (3) adding polyvinyl pyrrolidone and polyethyleneimine to the second mixed solution to obtain a third mixed solution;
[0157] (4) The third mixed solution was sheared for 30 min at a rotation speed of 400 rpm / min, and then ultrasonically treated for 30 min at a temperature of 0° C. and an ultrasonic power of 100 kW to obtain a catalyst slurry.
[0158] The mass percentage of the dispersant in the catalyst slurry is 2.5%, and the initial solid content of the catalyst slurry is 2%.
[0159] Example 14
[0160] (1) adding perfluorosulfonic acid resin to ethanol to obtain a first mixed solution;
[0161] (2) adding nickel ferrite to the first mixed solution to obtain a second mixed solution;
[0162] (3) adding polyvinyl pyrrolidone and cetyl trimethyl ammonium bromide to the second mixed solution to obtain a third mixed solution;
[0163] (4) The third mixed solution was sheared for 30 min at a rotation speed of 400 rpm / min, and then ultrasonically treated for 30 min at a temperature of 0° C. and an ultrasonic power of 100 kW to obtain a catalyst slurry.
[0164] The mass percentage of the dispersant in the catalyst slurry is 2.5%, and the initial solid content of the catalyst slurry is 2%.
[0165] Example 15
[0166] (1) adding perfluorosulfonic acid resin to ethanol to obtain a first mixed solution;
[0167] (2) adding nickel ferrite to the first mixed solution to obtain a second mixed solution;
[0168] (3) adding cetyltrimethylammonium bromide and hydroxyethyl cellulose to the second mixed solution to obtain a third mixed solution;
[0169] (4) The third mixed solution was sheared for 30 min at a rotation speed of 400 rpm / min, and then ultrasonically treated for 30 min at a temperature of 0° C. and an ultrasonic power of 100 kW to obtain a catalyst slurry.
[0170] The mass percentage of the dispersant in the catalyst slurry is 2.5%, and the initial solid content of the catalyst slurry is 2%.
[0171] Comparative Example 1
[0172] (1) adding perfluorosulfonic acid resin to ethanol to obtain a first mixed solution;
[0173] (2) adding nickel ferrite to the first mixed solution to obtain a second mixed solution;
[0174] (3) The second mixed solution was sheared for 30 min at a rotation speed of 400 rpm / min, and then ultrasonically treated for 30 min at a temperature of 0° C. and an ultrasonic power of 100 kW to obtain a catalyst slurry.
[0175] The initial solid content of the catalyst slurry is 10%.
[0176] Comparative Example 2
[0177] (1) adding perfluorosulfonic acid resin to ethanol to obtain a first mixed solution;
[0178] (2) adding nickel ferrite to the first mixed solution to obtain a second mixed solution;
[0179] (3) The second mixed solution was sheared for 30 min at a rotation speed of 400 rpm / min, and then ultrasonically treated for 30 min at a temperature of 0° C. and an ultrasonic power of 100 kW to obtain a catalyst slurry.
[0180] The initial solid content of the catalyst slurry is 2%.
[0181] Comparative Example 3
[0182] (1) adding perfluorosulfonic acid resin to ethanol to obtain a first mixed solution;
[0183] (2) Add nickel ferrite to the first mixed solution, stir and mix, and obtain a catalyst slurry.
[0184] The catalyst slurries prepared in Examples 1-15 and Comparative Examples 1-3 were allowed to stand at room temperature for 1 hour, and the sedimentation retention rates were calculated. The results are shown in Table 1:
[0185] Table 1 Comparison of sedimentation retention rates of catalyst slurries in different embodiments and comparative examples
[0186] Initial solid content (%) Solid content after standing (%) Sedimentation retention rate (%) Example 1 10 9.6 96 Example 2 10 9.6 96 Example 3 10 9.7 97 Example 4 10 9.6 96 Example 5 10 9.6 96 Example 6 10 9.8 98 Example 7 10 9.7 97 Example 8 10 7.2 72 Example 9 10 7.5 75 Example 10 1 0.95 95 Example 11 20 19.6 98 Example 12 2 1.96 98 Example 13 2 2 100 Example 14 2 2 100 Example 15 2 2 100 Comparative Example 1 10 1 10 Comparative Example 2 2 0.2 10 Comparative Example 3 10 0 0
[0187] As can be seen from Table 1, the catalyst slurries prepared in Examples 1-15 of the present application have significantly improved sedimentation retention rates relative to the catalyst slurries in Examples 1-3, indicating that the examples of the present application can significantly improve the sedimentation retention rate of the catalyst slurry by adding a dispersant to the catalyst slurry.
[0188] Among them, it can be seen from the comparison between Examples 1-7 and Examples 8-9 that in the process of preparing the catalyst slurry, by combining shear treatment and cell crushing treatment (ultrasonic treatment), the dispersion effect can be significantly improved, the stability of the catalyst slurry can be ensured, and the sedimentation retention rate of the catalyst slurry can be significantly improved.
[0189] From the comparison between Example 12 and Examples 13-15, it can be seen that when polyvinyl pyrrolidone and polyethyleneimine, polyvinyl pyrrolidone and hexadecyltrimethylammonium bromide, and a combination of hexadecyltrimethylammonium bromide and hydroxyethyl cellulose are used as dispersants in Examples 13-15, respectively, the dispersion effect can be improved, and the sedimentation retention rate is improved relative to Example 12 in which a single dispersant is used.
[0190] The above is a detailed introduction to the embodiments of the present application. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method and core idea of the present application. At the same time, for those skilled in the art, based on the ideas of the present application, there may be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A catalyst slurry, characterized in that: including catalyst, proton exchange resin, dispersant and solvent; Wherein, the dispersant includes at least one of polyvinyl pyrrolidone, polyvinyl alcohol, polyethylene imine, hexadecyltrimethylammonium bromide and hydroxyethyl cellulose.
2. The catalyst slurry according to claim 1, characterized in that The dispersant includes polyvinyl pyrrolidone and polyethylene imine; and / or, the dispersant comprises polyvinyl pyrrolidone and cetyltrimethylammonium bromide; And / or, the dispersant includes cetyltrimethylammonium bromide and hydroxyethyl cellulose.
3. The catalyst slurry according to claim 1, characterized in that The mass percentage of the dispersant in the catalyst slurry is 0.1% to 5%.
4. The catalyst slurry according to claim 1, characterized in that The particle size D90 of the colloidal particles in the catalyst slurry is 280nm to 350nm.
5. The catalyst slurry according to claim 1, characterized in that The zeta potential of the catalyst slurry is -35mV to -50mV.
6. The catalyst slurry according to claim 1, characterized in that In terms of mass percentage, the initial solid content of the catalyst slurry is 1% to 20%.
7. The catalyst slurry according to any one of claims 1 to 6, characterized in that After standing at room temperature for 1 hour, the sedimentation retention rate of the catalyst slurry is ≥95%.
8. A method for preparing a catalyst slurry, for preparing the catalyst slurry according to any one of claims 1 to 7, characterized in that: include: Proton exchange resin is provided; adding the proton exchange resin into a solvent to obtain a first mixed solution; adding a catalyst to the first mixed solution to obtain a second mixed solution; adding a dispersant to the second mixed solution to obtain a third mixed solution; The third mixed solution is dispersed to obtain catalyst slurry.
9. The method for preparing the catalyst slurry according to claim 8, characterized in that: The step of dispersing the third mixed solution comprises: The third mixed solution is subjected to shearing treatment and cell pulverization treatment.
10. The method for preparing the catalyst slurry according to claim 9, characterized in that: The shearing treatment conditions are: shearing for 10 min to 60 min at a rotation speed of 200 rpm / min to 600 rpm / min.
11. The method for preparing the catalyst slurry according to claim 9, characterized in that: The cell pulverization treatment conditions are: at a temperature of -5°C to 5°C, an ultrasonic power of 50kW to 150kW, and ultrasonic treatment for 10min to 60min.
12. A membrane electrode, characterized in that: including a catalyst layer; The catalyst layer is prepared by using the catalyst slurry according to any one of claims 1 to 7, or by using the catalyst slurry prepared by the method for preparing the catalyst slurry according to any one of claims 8 to 11.
13. An electrolytic cell, characterized in that: Comprising the membrane electrode according to claim 12.
Citation Information
Cited By
Multi-stage dispersion process-based membrane electrode anode catalyst slurry for PEM electrolyzed water as well as preparation method and application of multi-stage dispersion process-based membrane electrode anode catalyst slurry
CN122257042A